2007
DOI: 10.1002/jmri.20891
|View full text |Cite
|
Sign up to set email alerts
|

Transient signal changes in diffusion‐weighted stimulated echoes during neuronal stimulation at 3T

Abstract: Purpose: To develop a sensitive method for detecting minute transient signal changes that can arise due to variations in the extravascular apparent self-diffusion coefficient, D, during neuronal activation. Materials and Methods:A three-pulse sequence that reads out a moderately diffusion-weighted (DW) primary echo (PRE) and a heavily DW stimulated echo (STE) was employed to investigate whether small transient signal changes in extravascular D occur in response to a visual stimulus. Contributions to signal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In addition, for the B0 signal the corresponding mean percent signal change was 0.10% for the tactile task and 0.14% for the visual task. This pattern of a relatively large mean percent signal change for FA compared with the mean percent signal change in MD and B0 is more in line with the hypothesized activity-related morphological glial cell changes and suggests that the observed signal changes cannot be explained by hemodynamics alone (Song et al, 1996; Does et al, 1999; Goerke and Moller, 2007; Miller et al, 2007; Lu et al, 2009). Thus, a possible hemodynamic contribution (and if present by itself a valid and interesting contrast mechanism for measuring activation in white matter) may not fully explain the measured fDTI signal.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, for the B0 signal the corresponding mean percent signal change was 0.10% for the tactile task and 0.14% for the visual task. This pattern of a relatively large mean percent signal change for FA compared with the mean percent signal change in MD and B0 is more in line with the hypothesized activity-related morphological glial cell changes and suggests that the observed signal changes cannot be explained by hemodynamics alone (Song et al, 1996; Does et al, 1999; Goerke and Moller, 2007; Miller et al, 2007; Lu et al, 2009). Thus, a possible hemodynamic contribution (and if present by itself a valid and interesting contrast mechanism for measuring activation in white matter) may not fully explain the measured fDTI signal.…”
Section: Discussionsupporting
confidence: 64%
“…However, it was shown that gradient coupling between changes in extravascular susceptibility gradients (i.e., BOLD effect) and the diffusion gradients can result in substantial changes in ADC (Zhong et al, 1991; Hong and Dixon, 1992). These results implicate that DfMRI is not immune to possible hemodynamic effects and posed the question whether or not the reported DfMRI activity-related ADC changes can be fully explained by this gradient coupling effect (Song et al, 1996; Does et al, 1999; Goerke and Moller, 2007; Miller et al, 2007; Lu et al, 2009; Ding et al, 2012; Rudrapatna et al, 2012). Although the results presented in (Stroman et al, 2008; Flint et al, 2009; Tirosh and Nevo, 2013) do provide important evidence that neuronal activation significantly reduces water displacement that can be measured using DfMRI it does not provide information on the relative contributions of the different contrast mechanisms to the measured ADC changes in gray matter.…”
Section: Introductionmentioning
confidence: 84%
“…Figure 3c shows that the maximal relative signal change of the STE increases as a function of mixing time. This finding is consistent with previous observation, in which a larger relative signal change of the STE compared to the PRE was reported (24). Furthermore, the rise time and the signal undershoot after the stimulation period observed in the STE trial averages are very similar to the ones of the PRE, which shows the typical temporal characteristics of the BOLD response.…”
Section: Resultssupporting
confidence: 94%
“…Prior literature finding temporal equivalence between BOLD and DfMRI have cited this as evidence for dominance of the BOLD component in the diffusion signal (Goerke and Moller 2007; Yacoub et al. 2008; Rudrapatna et al.…”
Section: Discussionmentioning
confidence: 88%